دليل الحيران على مورد الظّمآن دراسة وتعليق -من بداية الكتاب إلى آخر شرح مقدمة الناظم. من ص4-ص33 - غدير عمر, كريمة; العايب, أماني; جاب الله, كريمة (University of Eloued-جامعة الوادي, 2022)
"تهدف الدِّراسة إلى إبراز عَلَمَين جليلين في عِلم الرَّسم والضَّبط ومؤلَّفَيهِما، أمَّا الأوّل: فهو الإمام الخرَّاز، والتَّعريف بِنَظمِه ((مورد الظمآن))، ومصادره في جمعه، ومنهجه في ذلك، وبيان قيمته العلميّة في علم الرَّسم والضَّبط، أَلْزَمْنا كلّ ذلك في المطلب الأول، من المبحث الأول، أمَّا المطلب الثاني فخُصِّص للكلام عن ثاني العَلمين: الإمام المارِغني، والتَّعريف بشرحِه ((دليل الحيران على مورد الظمآن))، ومكانته في صفوف العلم، ومنهجه فيه. ثم قمنا في المبحث الثاني بدراسة المسائل المهمَّة التي وردت في مقدٍّمة الكتاب، في خمسة مطالب، وأخيرا المبحث الثالث وفيه: تحقيق النَّص المخَصَّص والتَّعليق عليه من أوَّل الكتاب إلى آخر شرح مقدِّمة النَّاظم.""This study aims to highlight two great figures and authors in the science of the Quranic script and control. As for the first, it is Imam Al-Kharraz, and the definition of his book Mawrid Al Damaan, his sources in collecting it, his method in that, and the statement of its scientific value in the field of the Quranic script and control. This was discussed in the first part of the first chapter. As for the second figure, it was Al-Imam Al-Marghani, and the definition of his explanation Dalil Al Hairan Ala Mawrid Al Damaan, his position in the ranks of science, and his approach to it. The second chapter studied the important issues that were mentioned in the introduction to the book, in five aspects. The third chapter involved the investigation of the specific text and commenting on it from the beginning of the book to the last explanation of the author's introduction. "
مذكرة ماستر
Keywords: علم الرسم- الضبط- دليل الحيران; The science of drawing - tuning - a guide to confusion